2016
DOI: 10.3389/fenrg.2016.00002
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Terpenoid Content in Pine by Organic Solvent Extraction and Fast-GC Analysis

Abstract: Terpenoids, naturally occurring compounds derived from isoprene units present in pine oleoresin, are a valuable source of chemicals used in solvents, fragrances, flavors, and have shown potential use as a biofuel. This paper describes a method to extract and analyze the terpenoids present in loblolly pine saplings and pine lighter wood. Various extraction solvents were tested over different times and temperatures. Samples were analyzed by pyrolysis-molecular beam mass spectrometry before and after extractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
(79 reference statements)
1
17
0
Order By: Relevance
“…The Bacteroidetes family Muribaculaceae (was known as S24-7), accounting for ~8.3% of core microbiota in PVO, is a common bacterial family in herbivore gastrointestinal tracts; it has high potential for degradation of plant glycans and can be enriched by high-fat diets in laboratory mice [64][65][66][67][68][69] . Presumably, Muribaculaceae partially replaced the function of Firmicutes for cellulose degradation and may have promoted lipid absorption in gut microbiomes of TX and PVO that ate seeds with high lipid content 25,[29][30][31]70 .…”
Section: Discussionmentioning
confidence: 99%
“…The Bacteroidetes family Muribaculaceae (was known as S24-7), accounting for ~8.3% of core microbiota in PVO, is a common bacterial family in herbivore gastrointestinal tracts; it has high potential for degradation of plant glycans and can be enriched by high-fat diets in laboratory mice [64][65][66][67][68][69] . Presumably, Muribaculaceae partially replaced the function of Firmicutes for cellulose degradation and may have promoted lipid absorption in gut microbiomes of TX and PVO that ate seeds with high lipid content 25,[29][30][31]70 .…”
Section: Discussionmentioning
confidence: 99%
“…Terpenoids, such as β-pinene, myrcene, camphor, and cineole, a group of naturally occurring chemicals, have allelopathic effects as toxic, inhibitory or deterrent compounds ( Langenheim, 1994 ). Harman-Ware et al (2016) reported presence of monoterpenes, α- and β-pinene, camphene, and δ-carene in the terpenoids extract of loblolly pine saplings and pine lighter wood. The β-pinene and camphene are two important potential allelopathic compounds that may be present in pinebark mulch materials and responsible for inhibition of weed seed germination and growth.…”
Section: Allelochemicals In Common Landscape Mulch Materialsmentioning
confidence: 97%
“…As a result of the removal of the diphosphate group, the intermediate allyl cations can be subjected to a series of chemical cascades with the formation of various compounds with linear and/or cyclized hydrocarbon chains, which are then further modified by the addition of various functional groups and adducts [ 2 , 3 , 4 ]. This feature of terpenes and terpenoids creates their remarkable chemical diversity and requires an appropriate approach for extraction, detection, and purification [ 8 , 9 , 10 ].…”
Section: Extraction and Analysis Of Terpenoidsmentioning
confidence: 99%
“…The use of specific methods is determined depending on the size and complexity of a molecule, its physical properties (polarity, volatility), chemical properties, and some other parameters [ 7 ]. The polarity of a molecule is the most important feature that should be considered when determining the method of extraction, analysis, and purification of a substance [ 8 , 9 , 11 ].…”
Section: Extraction and Analysis Of Terpenoidsmentioning
confidence: 99%
See 1 more Smart Citation